Influences of alexithymia and assertiveness in the self-concept - study of women - Lopes, Rosa Cristina Correia (2011)
The self-concept, its importance has been widely investigated in different areas of knowledge and involved in numerous clinical situations, and is considered an entity in different vulnerable psychopathological disorders in women. We conducted a study aiming to identify some psychological characteristics that influence and / or predictors of self-concept in women, specifically, alexithymia and assertiveness. In this study, descriptive, correlational and cross, the instrument of data collection was composed of scales (validated in the Portuguese population); Self-concept Clinical Inventory (SCCI) Toronto Alexithymia Scale (TAS20) and Rathus Assertiveness Scale (RAS). The convenience sample consisted of 104 female students in the Bachelor of Nursing, aged between 18 and 35 years, mean age 19,32 years and standard deviation 1,7. The self-concept varied between 58 and 94 (minimum-maximum), with an mean of 74,06 and 72,00 of mode. Correlational study found that alexithymia (TAS20) (rho =−,426; p = ,000) and its factors: identifying feelings (F1-TAS20) (rho =−,270; p = ,006), describe feelings (F2-TAS20) (rho =−,392; p = ,000) and externally oriented thinking (F3-TAS20) (rho = ,372; p = ,000) correlated negatively and highly significantly with self-concept. Assertiveness correlated positively and highly significantly with self-concept (rho = ,412; p = ,000). Through hierarchical multiple regression predictor variables emerged as the self-concept: alexithymia (2,25%;p = ,000 negative contribution), assertiveness (2,64%; p = ,002 positive contribution) externally oriented thinking (2,92%; p = ,008 negative contribution). We conclude that the implementation of strategies which promote personal and social development and personal and social skills of women, particularly assertiveness and expression of emotions are essential to a better self-concept and consequently to the mental health of women.